Berberine alleviates ETEC-induced intestinal inflammation and oxidative stress damage by optimizing intestinal microbial composition in a weaned piglet model - Wang, Yue; Zhang, Ziting; Du, Min; Ji, Xu; Liu, Xiaodan; Zhao, Chunfang; Pang, Xunsheng; Jin, Erhui; Wen, Aiyou; Li, Shenghe; Zhang, Feng (Frontiers in Immunology, 2024)
Enterotoxigenic Escherichia coli (ETEC) is the main diarrhea-causing pathogen in children and young animals and has become a global health concern. Berberine has used in treating gastrointestinal disorders and bacterial diarrhea in China for a long history. In this study, we explored the effects of berberine on growth performance, intestinal inflammation, oxidative damage, and intestinal microbiota in a weaned piglet model of ETEC infection. Twenty-four piglets were randomly divided into four groups—a control group (fed a basal diet [BD] and infused with saline), a BD+ETEC group (fed a basal diet and infused with ETEC orally administered to piglets at 1 × 109 CFU per pig), a LB+ETEC group (fed a basal diet with 0.05% berberine and infused with ETEC orally administered to piglets at 1 × 109 CFU per pig), and a HB+ETEC group (fed a basal diet with 0.1% berberine and infused with ETEC orally administered to piglets at 1 × 109 CFU per pig). The feeding adaptation period lasted for 5 days and the experiment period lasted for 21 days. Berberine significantly improved the final body weight (BW), average daily gain (ADG), and average daily feed intake (ADFI) (P<0.05) of piglets, and effectively decreased the incidence of diarrhea among the animals (P<0.05). Additionally, berberine significantly downregulated the expression levels of the genes encoding TNF-α, IL-1β, IL-6, IL-8, TLR4, MyD88, NF-κB, IKKα, and IKKβ in the small intestine of piglets (P<0.05). ETEC infection significantly upregulated the expression of genes coding for Nrf2, CAT, SOD1, GPX1, GST, NQO1, HO-1, GCLC, and GCLM in the small intestine of the animals (P<0.05). Berberine significantly increased the relative abundance of beneficial bacteria and decreased that of pathogenic bacteria known to be closely related to intestinal inflammation and oxidative stress in piglets. In conclusion, ETEC infection disrupted the intestinal microbiota in weaned piglets, upregulating the TLR4/MyD88/NF-κB and Nrf2 signaling pathways, and consequently leading to intestinal inflammation and oxidative stress-induced damage. Our data indicated that berberine can optimize intestinal microbiota balance and modulate the TLR4/MyD88/NF-κB and Nrf2 signaling pathways, thus helping to alleviate intestinal inflammation and oxidative damage caused by ETEC infection in weaned piglets.